Examining the Causal Relationship between Financial Intermediation and Poverty in Selected Developing Countries - Magwedere, Margaret R.; Chisasa, Joseph; Marozva, Godfrey (International Journal of Economics and Financial Issues, 2022)
Formal financial intermediation and the financial dimensions which include financial efficiency, financial access and financial stability can be tools that can be useful in providing the much needed finance for households and businesses. The objective of this article is to examine the causal relationship between financial dimension in the financial intermediation setting and poverty. This study used annual data from 2004 to 2018 for a panel of selected developing countries. The pooled mean group estimator in a panel ARDL framework was employed to examine the causal relationship between financial dimensions and poverty. Results revealed a long run causal relationship between the financial dimensions and poverty with no significant short run causal relationships. Furthermore, the study highlights the great importance of multidimensionality of poverty and that how poverty is measured is significant to the nature of the causal links with financial dimensions. The findings are expected to encourage developing countries to particularly pay attention to how poverty is measured and how different financial dimensions are important for an inclusive financial system.